The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25112663
|View full text |Cite
|
Sign up to set email alerts
|

Response Factorial Design Analysis on Papain-Generated Hydrolysates from Actinopyga lecanora for Determination of Antioxidant and Antityrosinase Activities

Abstract: Actinopyga lecanora (A. lecanora) is classified among the edible species of sea cucumber, known to be rich in protein. Its hydrolysates were reported to contain relatively high antioxidant activity. Antioxidants are one of the essential properties in cosmeceutical products especially to alleviate skin aging. In the present study, pH, reaction temperature, reaction time and enzyme/substrate ratio (E/S) have been identified as the parameters in the papain enzymatic hydrolysis of A. lecanora. The degree of hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Data were linearly distributed, indicating that there were no aberrates in the residual of the results. Therefore, it was concluded that the data had a normal distribution, which was in accordance with the findings of Bahari et al (2020), in which the data plot of the DPPH radical scavenging activity obtained for sea cucumber (Actinopyga lecanora) hydrolysate was normally distributed. Furthermore, the residuals of the results were evenly distributed between positive and negative values, indicating that the data were independent with stable variance (data not shown).…”
Section: Results Of the Central Composite Designsupporting
confidence: 84%
“…Data were linearly distributed, indicating that there were no aberrates in the residual of the results. Therefore, it was concluded that the data had a normal distribution, which was in accordance with the findings of Bahari et al (2020), in which the data plot of the DPPH radical scavenging activity obtained for sea cucumber (Actinopyga lecanora) hydrolysate was normally distributed. Furthermore, the residuals of the results were evenly distributed between positive and negative values, indicating that the data were independent with stable variance (data not shown).…”
Section: Results Of the Central Composite Designsupporting
confidence: 84%
“…The hydrophobic amino acids are remarkably responsible for the antioxidant activities of enzymaticallyhydrolyzed protein [Ghanbari et al, 2015]. Among them, leucine, valine, methionine, and alanine as well as aromatic amino acids, such as tyrosine, histidine, and phenylalanine play a key role in peptide activity in the DPPH assay [Bahari et al, 2020]. Analysis of the amino acid profile of BH indicated the presence of these amino acids with significant contents, as shown in Table 1.…”
Section: Antioxidant Activities Of Bhmentioning
confidence: 99%
“…On the other hand, the amino acid profile of BH showed that there were significant contents of histidine, tyrosine, and phenylalanine, which together with high contents of leucine and valine (Table 1), could be related to antioxidant activities of protein hydrolysate of hybrid sturgeon. Bahari et al [2020] reported that the presence of the mentioned amino acids in the peptide sequences enhanced their antiradical activity.…”
Section: Amino Acid Profile Of Hydrolysatementioning
confidence: 99%
“…Bahari et al. studied the best conditions for the preparation of antioxidant SCP via response factorial design analysis under various pH conditions, reaction temperatures, reaction time, and enzyme/substrate ratios using papain . They found the best conditions to be pH 5, 70 °C, and 9 h in 1.00% enzyme/substrate ratio.…”
Section: Production Of Sea Cucumber Peptidesmentioning
confidence: 99%